Maturidade da dimensão "modelo de negócios" em uma indústria termoplástica com vistas à transformação digital na indústria 4.0 - Luz, Marcus Vinicius Oliveira da (Brasil, 2024)
This work assesses the maturity of the business model dimension in a thermoplastic industry, with a view to digital transformation in industry 4.0. For this, a bibliographic analysis was performed to obtain information about the size of the business model in a thermoplastic industry and the challenges to develop business models that differentiate their products, as well as the maturity of this business model to keep up with digital transformation in industry 4.0. Furthermore, the work considered the theory and context of case studies reported in the literature and used the case study as a research method. Data was extracted from the pimm 4.0 system, which allowed to assess the maturity of the business model dimension. The results suggest that the business model in the investigated industry must be improved through product development and improvement to keep up with the speed at which digital transformation occurs. At the end of this investigation, it was possible to find that the thermoplastic industry faces challenges in developing unique business models that can differentiate its products